How to Make Notes and Write - Allosso, Dan; Allosso, S.F (Open textbook library., 2019)
There are plenty of personal knowledge management systems out there, promising to help you take smart notes or link your thinking or build a second brain. And there are plenty of writing guides out there promising to teach you the elements of style. This book offers a simple and effective way to make effective notes on sources and your interpretations of them, then turn those thoughts into clear and compelling output.